Software Geogebrano ensino da trigonometria: proposta metodológica e revisão da literatura a partir das produções discentes nas dissertações do PROFMAT - SOUSA, Francisco Deilson Rodrigues Barbosa de (2018)
In order to understand the impact of the use of Geogebra software in the teaching of trigonometry as a tool to improve learning, this work proposes to carry out a literature review based on the dissertations of the Professional Master in Mathematics in National Network - PROFMAT developed in the last five years . For this, a research was proposed in the PROFMAT database with the use of the words trigonometry, trigonometric functions, sine and radian function, resulting in 134 registers, where 20 papers were selected according to the following selection criteria: complete studies Geogebra assistance, regular high school assignments, and executable files. It was verified that the dissertations, most of which were defended in 2013 (30.0%), presented diverse objectives, such as face-to-face activities with teachers or students and the proposal of didactic activities on the use of software. It was found that Bahia was the state with the highest number of studies (15.0%), where the most frequent theme was trigonometric functions, represented by 29.0% of the studies. For the most part, the dissertations presented 45.0% of studies based on methodological delineations. It is concluded that Geogebra is an important active methodology that assists the teaching of trigonometry of regular high school students, recognized by mathematics teachers, but still considered by a portion of these professionals, a barrier in the use of the tool in the classroom, due to the limitations in its handling. It is essential to reflect on the importance of active methodologies in the classroom, especially Geogebra, since they are of great relevance for the construction of mathematical knowledge, contributing for students to develop a creative thinking and potentializing their understanding, minimizing their difficulties and thus increasing their interest in Trigonometry.